Psychological Stress and Perceived Self-Efficacy in Mothers of Autistic Children - Azeem Mubarak, Doaa Mohammed Abdul (Journal of Intellectual Disability - Diagnosis and Treatment, 2022)
Background: Literature has indicated that parents of autistic children face higher stress levels than parents of allistic children (non-autistic children), leading them to experience depressive symptoms that impact their daily lives, reducing their quality of life. This study aims to investigate the relationship between psychological stress and perceived self-efficacy in mothers and fathers of autistic children. Methods: This study is descriptive and cross-sectional. A total of 125 mothers and fathers consented to participate in the current study. 15 parents only partially completed the survey, so their data was not included. The remaining 110 cases were included. This left a final sample of 110 parents of autistic children, 100 mothers (90.9 %), and 10 fathers (9.1%). All were biological parents. Results: As indicated by the results, all statements in the Parental distress (PD) subscale had a score ranging between high (the majority of items, 10) to medium (two items). All statements in the Parent-Child Dysfunctional interaction (P-CDI) subscale had a score ranging between high (the majority of items, 10) to low (two items). All statements in the Difficult Child (DC) subscale scored high. The whole subscale had a mean score of 4.04 (SD=3.17) with a high score. For correlations, psychological stress was negatively correlated with perceived self-efficacy (r = -0. 34, p < 0.001). Conclusion: The stress experienced during the nurturing of children with disabilities is a factor that threatens the psychological well-being of mothers of autistic children.